Interspecies Communication: An Introduction and a Provocation. (1st June 2019) - Tromble, Meredith
Both an introduction to PUBLIC #59 and a rumination on the difficulty of interspecies communication, this essay argues for art and interspecies communication as means of building mental and emotional qualities useful for re-imagining culture in a time of rapid environmental change, embedding a self-reflexive example in the text.